RISK FACTORS OF HIGH BLOOD PRESSURE IN CHILDREN EXPOSED TO PASSIVE SMOKE - Fitri, Agita Diora; Mariana, .; Ismah, Zata; Irfani, Tri Hari; Gufron, Muhammad; Adil, Muhammad (LIFE: International Journal of Health and Life-Sciences, 2018)
Indonesian awareness about environmental tobacco smoke is so low due to the cultural habit of smokers, according to SDKI 2012, passive smoker in South Sumatra was increase 82,5%. The previous research was found that under 5 years old children with low birth weight was 6,3%, short stature was 7% and very tiny was 1% (FE-UI 2010). Children exposed to tobacco smoke accompanied by high blood pressure are in greater chance in developing severe cardiovascular disorders in adulthood. This study aimed to determine the effects of secondhand tobacco smoke exposure and other variables that affect blood pressure in passive smoker children in Palembang. This study was conducted with cross-sectional design involving 160 samples age between representing each district. It was found that 100% sample are second hand smoker. This study result was the most dominant risk factors influencing systolic blood pressure were birth weight, with higher incidence of elevated systolic blood pressure (p = 0.024; 95% CI = (- 7.75) - (- 0.511)), followed by tobacco smoke exposure (p = 0.042; 95% CI = 0.093-0.521). Every tobacco smoke exposure could increase systolic pressure each 0,608 point, 0,307 point and 1,865 point. Future scope of this research are using spirometry test for better result, more samples and compares it with others future risk factors.